Problem Based Learning on Socio-Scientific Issues to Strengthen Students’ Environmental Care Character at Ban Buketamong School Friendship 128, Cho Airong, Narathiwat, Thailand - Taufik Hidayat; Ainun Mardiyah Lubis; Syahruddin Aritonang; Maryam bnesa; Darwis Lubis (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effect of Problem Based Learning integrated with socio-scientific issues on strengthening students’ environmental care character at Ban Buketamong School Friendship 128, Cho Airong, Narathiwat, Thailand. The research employed a pre-experimental one-group pretest–posttest design involving 30 Grade 8 students. Data were collected using a 25-item environmental care character questionnaire and analyzed through descriptive statistics and a paired sample t-test. The results showed that the mean score increased from 67.37 in the pretest to 82.80 in the posttest. The paired sample t-test indicated a significant difference between pretest and posttest scores (p < 0.05), with a large effect size (Cohen’s d = 10.28). These findings demonstrate that Problem Based Learning based on socio-scientific issues significantly enhances students’ environmental awareness, responsibility, participation, and sustainable behavior. The integration of authentic environmental problems into learning activities provides meaningful opportunities for students to develop responsible attitudes and moral reflection toward environmental challenges. Therefore, this instructional approach is recommended to promote environmental care character among junior secondary school students.